Determination of Reference Interval for Serum Homocysteine, Magnesium, and Uric Acid from Tertiary Care Hospital Data By the Bhattacharya Method - Monica Peter; Arunachalam Vijaya Bhaskar; Videeta Avinash Kamble; Gaikwad Abhishek Lazaras; Pamela Christudoss; Joe Varghese; Padmanaban Venkatesan (Current Medical Issues, 2024)
Introduction: Direct ways of establishing reference intervals for analytes are time-consuming and costly. Bhattacharya analysis is an indirect way to mathematically derive reference intervals from the results of analytes in a hospital database and is practically a simple and inexpensive alternative to direct methods. Methods: Data of serum uric acid, magnesium, and plasma homocysteine levels measured in the department of clinical biochemistry over 3 years were extracted from the hospital database along with the age, gender, and location of the patients. Bhattacharya analysis was performed by identifying underlying Gaussian distribution within the non-Gaussian distribution of the patient data by log transformation of the distribution of the data. Reference intervals for each of the analytes were calculated from the identified Gaussian distribution. Results: The reference interval for serum uric acid was 1.49–8.97 mg/dL in men and 2.13–6.14 in women, serum magnesium in adults was 1.19–3.21 mg/dL, and plasma homocysteine in adults was 4.6–21 μg/dL. Conclusion: Using Bhattacharya analysis, we were able to derive reference intervals for analytes from our hospital data.